2020
DOI: 10.3389/fphys.2020.617459
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Modulation for Cardiovascular Disease

Abstract: Dysfunction of the autonomic nervous system has been implicated in the pathogenesis of cardiovascular disease, including congestive heart failure and cardiac arrhythmias. Despite advances in the medical and surgical management of these entities, progression of disease persists as does the risk for sudden cardiac death. With improved knowledge of the dynamic relationships between the nervous system and heart, neuromodulatory techniques such as cardiac sympathetic denervation and vagal nerve stimulation (VNS) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 184 publications
(341 reference statements)
0
67
0
Order By: Relevance
“…Ganglia may contain 200–1,000 neurons (Armour et al, 1997 ; Pauza et al, 2000 ; Choi et al, 2017 ), including sympathetic and parasympathetic efferent neurons, afferent neurons and local interneurons, that receive inputs from both efferent and afferent neurons. Studies have shown that GPs are important mediators in the interaction of the intrinsic CANS with the extrinsic CANS (Hadaya and Ardell, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ganglia may contain 200–1,000 neurons (Armour et al, 1997 ; Pauza et al, 2000 ; Choi et al, 2017 ), including sympathetic and parasympathetic efferent neurons, afferent neurons and local interneurons, that receive inputs from both efferent and afferent neurons. Studies have shown that GPs are important mediators in the interaction of the intrinsic CANS with the extrinsic CANS (Hadaya and Ardell, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence that more severe cardiac effects are produced by r-VNS is mixed and varies according to the model species used ( Ardell and Randall, 1986 ; Lockard et al, 1990 ; Lewis et al, 2001 ; Krahl et al, 2003 ). Due to its hypothesized cardiac effects, right cervical VNS is now under investigation for the treatment of heart failure ( Zannad et al, 2015 ; Gold et al, 2016 ; Anand et al, 2020 ; Hadaya and Ardell, 2020 ). While r-VNS has been safe and well-tolerated in these trials, it was found to be ineffective ( Zannad et al, 2015 ; Gold et al, 2016 ), or no more effective than l-VNS ( Premchand et al, 2014 , 2016 ; Nearing et al, 2021 ), at improving cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the extrathoracic extracardiac components include nodose ganglia, dorsal root ganglia and various areas within the spinal cord and brainstem that are involved in cardiovascular regulation (Fig. 1 ) [ 2 , 25 ].
Fig.
…”
Section: Cardiac Neuraxismentioning
confidence: 99%